Spillover Effects of the SEC's Regulatory Oversight on Private Debt Contracting: Evidence from Cross‐listed Foreign Firms - Chy, Mahfuz; Khurana, Inder K.; Kyung, Hoyoun (Journal of Accounting Research, 2025)
ABSTRACT We examine the effect of the Securities and Exchange Commission's (SEC) regulatory oversight on private debt contracting outcomes, using the signing of the multilateral memorandum of understanding (MMoU) as a natural experiment. The MMoU enables the SEC to take stricter punitive actions against wealth expropriation by cross‐listed firms’ insiders and enforce better compliance with applicable rules and regulations. We find that enhanced SEC oversight in the post‐MMoU regime lowers loan spreads by 36 basis points, thus saving an average cross‐listed firm approximately $9 million in direct loan costs over the life of a bank loan. Cross‐sectional analyses show that the effect is more pronounced for borrowers from countries with weaker institutions, borrowers with greater accounting discretion, and for loans arranged by top lenders or loans not secured by collateral. Conversely, the effect is less pronounced for borrowers who use IFRS or when the SEC faces greater budgetary constraints. Enhanced SEC oversight also leads to an increase in loan maturity and a decrease in financial covenants. Our evidence suggests that while the SEC's primary mandate is to protect public equity and bond investors, its supervision yields substantial borrowing cost savings and more lenient nonprice loan terms in the private debt markets as well.